Biowaste material reinforced cyanate ester based epoxy composites for flame retardant applications. (October 2016) - Krishnadevi, Krishnamoorthy; Selvaraj, Vaithilingam
This article reports the development of halogen-free flame-retardant amine-terminated cyclophosphazene (ATCP) and functionalized rice husk ash (FRHA)-reinforced cyanate ester (CE; 2, 2-bis(4-cyanatophenyl)propane)-based epoxy (EP) composite material through the ring formation of cyanurate and imino carbonyl adduct formation. The ATCP/FRHA/CE-EP composites were characterized using Fourier transform infrared spectroscopy, scanning electron microscope, X-ray diffraction analysis and contact angle measurements. A plausible fire-retardant mechanism has been hypothesized based on the analysis of decomposition temperature, char yield, heat release rate, total smoke production, smoke production rate and carbon monoxide production. These results suggest that the ATCP/FRHA/CE-EP composites can be used as hydrophobic, electrical-resistant and improved fire-retardant materials. Hence, ATCP/FRHA/CE-EP flame-retardant system paves new possibility of high-performance non-halogen flame-retardant polymeric materials for electronic and microelectronic applications.